Metastases of non-thyroidal tumors to the thyroid gland: a regional survey in middle franconia - Cordes, M.; Kuwert, Torsten (Experimental and Clinical Endocrinology and Diabetes, 2014)
Metastases of non-thyroidal tumors to the thyroid gland are infrequently diagnosed in the clinical environment. In autopsy studies, however, metastases to the thyroid gland have a frequency of 1.25-24%. The aim of this investigation was to explore the primary tumor and latency of diagnosis in patients who were diagnosed with metastases to the thyroid gland in 70 institutions associated to a scientific board in Middle Franconia during a 12 year period.Retrospective cross-sectional study.After a clinical data base research, 35 patients (21 male, 14 female) with a histological diagnosis of a secondary thyroid malignancy were identified between 2002 and 2013. The mean age of the patients at diagnosis of the metastasis was x=68.2 years (median: 70, standard deviation SD=± 8.4, range 46-85 years). The majority of the patients had metastases from renal cell carcinomas (n=19). In the other patients metastases from gastrointestinal carcinomas (n=2), bronchial carcinomas (n=3), malignant melanomas (n=3), sarcomas (n=2), and other tumors (n=6) were diagnosed. The time interval between the diagnosis of the primary tumor and the metastasis to the thyroid gland was different for patients with metastases from renal cell carcinomas and non-renal cell carcinomas (p<0.001, chi-test).In agreement with previous studies, the majority of metastases to the thyroid gland derive from renal cell carcinomas. In patients with non-renal malignancies, metastases to the thyroid gland are diagnosed simultaneously with the primary tumor to a higher proportion compared with metastasis from renal malignancies.
EVALuna2:13823